Public Private Partnerships for Municipal Waste Management in the City of Johannesburg - Madiba, Dineo (University of the Witwatersrand, Johannesburg, 2023)
Municipal solid waste management is increasingly becoming a burden while population growth, urbanisation and economic growth have overwhelmed the municipalities capacity to deliver waste services. In response municipalities are increasingly implementing public private partnerships to meet the growing demand for waste services. This qualitative study was conducted in the City of Johannesburg and focuses on investigating the challenges of public private partnerships for the delivery of waste services more specifically the study will focus on the Separation at Source program. Thirteen interviews were conducted involving participants from Pikitup, co-operatives, private companies, and an NGO. Interview guides were developed and interview questions were informed by the theoretical framework and themes identified in the literature review. Other sources of information consulted included legislative frameworks as well as Pikitup’s business plan. The results of this study indicate several challenges in the partnership model used to implement the Separation at Source program and the challenges can be summarised as institutional, financial, operational, and technical all of which are preconditions necessary to make partnerships work. It was also observed that stakeholder consultation and participation was inadequate leading to a lack of buy-in from key stakeholders
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management (in the field of Governance and Management) to the Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2023
Keywords: Waste management; Public private partnerhip; City of Johannesburg; UCTD; SDG-15: Life on land